Masking Level Difference and Electrophysiological Evaluation in Adults with Normal Hearing - Santiago, Joyce Miranda; Luiz, Cyntia Barbosa Laureano; Garcia, Michele; Gil, Daniela (International Archives of Otorhinolaryngology, 2020)
Introduction The auditory structures of the brainstem are involved in binaural interaction, which contributes to sound location and auditory figure-background perception.Objective To investigate the performance of young adults in the masking level difference (MLD) test, brainstem auditory-evoked potentials (BAEPs) with click stimulus, and frequency-following response (FFR), as well as to verify the correlation between the findings, considering the topographic origin of the components of these procedures.Methods A total of 20 female subjects between 18 and 30 years of age, with normal hearing and no complaints concerning central auditory processing underwent a basic audiological evaluation, as well as the MLD test, BAEP and FFR.Results The mean result on the MLD test was of 10.70 dB. There was a statistically significant difference in the absolute latencies of waves I, III and V in the BAEPs of the ears. A change in the FFR characterized by the absence of the C, E and F waves was noticed. There was a statistically significant difference in the positive correlation of wave V in the BAEPs with the MLD. There was a statistically significant difference in the positive correlation of the mean MLD and the V, A and F components of the FFR.Conclusion The mean MLD was adequate. In the BAEPs, we observed that the click stimulus transmission occurred faster in the right ear. The FFR showed absence of some components. The mean MLD correlated positively with the BAEPs and FFR.
Keywords: auditory perception; electrophysiology; brainstem; perceptual masking; adult